2015
DOI: 10.1093/nar/gkv389
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis reveals that human OASL binds dsRNA to enhance RIG-I signaling

Abstract: The oligoadenylate synthetase (OAS) enzymes are cytoplasmic dsRNA sensors belonging to the antiviral innate immune system. Upon binding to viral dsRNA, the OAS enzymes synthesize 2′-5′ linked oligoadenylates (2-5As) that initiate an RNA decay pathway to impair viral replication. The human OAS-like (OASL) protein, however, does not harbor the catalytic activity required for synthesizing 2-5As and differs from the other human OAS family members by having two C-terminal ubiquitin-like domains. In spite of its lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 69 publications
4
44
0
Order By: Relevance
“…Further, while human OASL lacks enzymatic activity, mouse OASL2 and chicken OASL have retained their ability to produce 2-5A (Eskildsen, Justesen, Schierup, & Hartmann, 2003). Human OASL is nonetheless an important part of innate immunity and is thought to have evolved to exert its antiviral effect by binding RIG-I and enhancing its signaling (Ibsen et al, 2015;Zhu et al, 2014). Loss-of-function mutations in primate OAS1 have also been identified that substantially impair 2-5A synthesis or completely eliminate enzymatic activity altogether (Carey et al, 2019).…”
Section: Box 1 the Innate Immune Systemmentioning
confidence: 99%
“…Further, while human OASL lacks enzymatic activity, mouse OASL2 and chicken OASL have retained their ability to produce 2-5A (Eskildsen, Justesen, Schierup, & Hartmann, 2003). Human OASL is nonetheless an important part of innate immunity and is thought to have evolved to exert its antiviral effect by binding RIG-I and enhancing its signaling (Ibsen et al, 2015;Zhu et al, 2014). Loss-of-function mutations in primate OAS1 have also been identified that substantially impair 2-5A synthesis or completely eliminate enzymatic activity altogether (Carey et al, 2019).…”
Section: Box 1 the Innate Immune Systemmentioning
confidence: 99%
“…MEX3C (Mex-3 RNA binding family member C), another recently identified E3 ligase, also mediates Lys63-Ub at K99 and K169 of CARD, playing a critical role in RIG-I activation (55). In addition, the oligoadenylate synthetases-like (OASL) protein, although not an E3 ubiquitin ligase itself, contains a dsRNA-binding groove and enhances RIG-I activation by mimicking the K63-linked pUb through its ubiquitin-like (UBL) domain (56,57). Non-covalent binding of K63-ubiquitin chains to CARDs also potently activates RIG-I (58).…”
Section: Posttranslational Control Of Rig-i Ubiquitinationmentioning
confidence: 99%
“…Whether viral infection was antagonized or accelerated depended on the timing and duration of type one IFN signaling. Other factors that can control properties of IFN signaling and impact outcome include various negative regulatory proteins like RNF125 that can influence the ubiquitination of PRRs [84], OASL that physically inhibits RIG-I [85,86], USP18 that displaces JAK2 from the type one IFN receptor [87], and multiple other proteins that dynamically regulate IFN signaling [88]. …”
Section: Opposing Functions Of Interferon Signaling In Cancermentioning
confidence: 99%